Reward dan Punishment dalam Perspektif Pendidikan Islam - Bahruddin Zaini (CENDEKIA: Jurnal Studi Keislaman, 2022)
Reward and punishment both are known as educational reaction through an action that have been done by students. rewards used tobe given for commendable act and punishments for the opposite one. Both are included in the educational media and arises as a form of effort to improve the behavior and character building of the students. The award is given as a form of expression of happiness and pride (appreciation) for the good deeds and achievements, while the punishment is given to evaluate and improve, not to judge, rebuke or revenge. These reward and punishment are necessary tobe implemented in the world of education.